2019
DOI: 10.3899/jrheum.181043
|View full text |Cite
|
Sign up to set email alerts
|

OMERACT Hip Inflammation Magnetic Resonance Imaging Scoring System (HIMRISS) Assessment in Longitudinal Study

Abstract: Objective.To assess reliability, feasibility, and responsiveness of Hip Inflammation Magnetic resonance imaging Scoring System (HIMRISS) for bone marrow lesions (BML) in hip osteoarthritis (OA).Methods.HIMRISS was scored by 8 readers in 360 hips of 90 patients imaged pre/post-hip steroid injection. Pre-scoring, new readers trained online to achieve intraclass correlation coefficient (ICC) > 0.80 versus experts.Results.HIMRISS reliability was excellent for BML status (ICC 0.83–0.92). Despite small changes po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…[56][57][58][59] We have previously reported that BML may change within an 8-week window in patients with hip OA undergoing imaging-guided intra-articular injections of steroid. 60 This repair hypothesis is further supported by limited data from therapeutic studies of patients with knee OA and BML where drugs targeting bone remodeling, such as bisphosphonates and strontium ranelate, led to a reduction in size of BMLs, reduced pain and cartilage loss, and delayed need for total knee replacement. 13,14 In addition, tumor necrosis factor inhibitors, which may reduce vascularization, have also been shown to reduce BMLs in OA.…”
Section: Discussionmentioning
confidence: 97%
“…[56][57][58][59] We have previously reported that BML may change within an 8-week window in patients with hip OA undergoing imaging-guided intra-articular injections of steroid. 60 This repair hypothesis is further supported by limited data from therapeutic studies of patients with knee OA and BML where drugs targeting bone remodeling, such as bisphosphonates and strontium ranelate, led to a reduction in size of BMLs, reduced pain and cartilage loss, and delayed need for total knee replacement. 13,14 In addition, tumor necrosis factor inhibitors, which may reduce vascularization, have also been shown to reduce BMLs in OA.…”
Section: Discussionmentioning
confidence: 97%
“…Bone marrow lesions (BML) in the hip are assessed on fluid-sensitive MRI scans using an electronic overlay on a webbased interface positioned over the femoral head and extending into the acetabulum on consecutive coronal slices through the hip joint (scoring range 0-100) (Figure 1) [57]. It has been shown to have very good to excellent reliability for detecting change in BML for patients with OA receiving glucocorticoid injections [58]. In the KIMRISS method, BML is scored using specific web-based electronic overlays for the femur, tibia, and patella on consecutive sagittal slices through the knee joint (scoring range 0-500) (Figure 2) [56].…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…For adults with rheumatoid arthritis, several validated scoring systems for hip involvement exist, including the Hip Inflammation Magnetic Resonance Imaging Scoring System (HIMRISS) and Hip Osteoarthritis MRI Scoring System (HOAMS) [ 10 , 11 ]. For children, however, although several scoring systems have been proposed [ 12 16 ], no child- and hip-specific scoring system including both inflammatory and permanent changes has been validated [ 17 ].…”
Section: Introductionmentioning
confidence: 99%